Examining the Electronic Customer Satisfaction in Enhancing E-Customer Loyalty: A Case of Pakistani Banking Sector (Journal of Asian Development Studies, 2023)
The main objective of the current study is to examine e-customer loyalty in the Pakistani banking sector by combining the expectancy theory and incorporating the mediating impact of electronic customer satisfaction on the relationship between electronic customer loyalty, efficiency, user friendliness, responsiveness, and reliability. Data have been collected through a close-ended questionnaire for data collection from the consumers of Pakistan by using the survey method. A structured questionnaire-based quantitative research approach will be used to gather data. A significant portion of the questionnaires received was deemed suitable for in-depth analysis. 260 out of 300 submitted questionnaires were eligible for further examination, as 40 respondents partially filled in their responses. The SERVQUAL model examines e-customer loyalty in the Pakistani banking sector. Five hypotheses were made, and the results showed a positive impact, while the results did not support four mediating hypotheses. The study's conclusions offer a wide range of theoretical and practical recommendations for bank management that aim to improve the security and usability of online banking websites while fostering consumer loyalty and confidence. This study offers valuable insights to promote consumer confidence in online banking services.